Features of photoinduced charge transfer in photomagnetic garnets YIG:Si and YIG:Co - Davidenko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Features of charge transfer under influence of linearly polarized light in photomagnetic garnets YIG:Si and YIG:Co are clarified. Comparative analysis of these two gernets is necessary to create a basis for the theoretical model of photoinduced magnetic effects (PME) in garnets and in other materials as well as for explanation of experimental results of PME observation in YIG:Co even at room temperatures. Known experimental results for YIG:Co are adequately explained and described within the scope of developed simplified theoretical model.